Pengaruh Kepemimpinan yang Memberdayakan, Komitmen Afektif terhadap Berbagi Pengetahuan: Peran Moderasi Budaya Kolaborasi - Febrie Sani Pangaribuan; Alice Salendu (Humanitas (Jurnal Psikologi), 2022)
Companies will get many benefits if they encourage employees to share their knowledge. Knowledge-sharing activities will improve individual, team, and company performance. The purpose of this study is to investigate the mediating role of affective commitment between empowering leadership and knowledge sharing as well as the moderating role of collaborative culture between empowering leadership and knowledge sharing mediated by affective commitment using data collected from 84 employees in X company by accidental sampling technique.  The scales of measurement adopted were empowering leadership scales (Yun et al., 2006), affective commitment scales (Rhoades & Eisenberger, 2001), collaborative culture scales (Pérez López et al., 2004), and knowledge sharing scales ( Hooff & Ridder, 2004). The results find the full mediating role of affective commitment and show that empowering leadership significantly impacts knowledge sharing (β = 0.20; SE = 0.108; 95%CI [0.513.0.475]). There is no conditional role of collaborative culture on the interaction of leadership empowerment, affective commitment, and knowledge sharing (β=0,058; p>0,05; 95%CI [-0,115.0,189]).  Companies can encourage employees to share their knowledge by empowering leadership, as this leadership style can build knowledge transfer among employees by creating affective commitment.